2013
DOI: 10.1007/s12651-013-0137-y
|View full text |Cite
|
Sign up to set email alerts
|

Is innovative firm behavior correlated with age and gender composition of the workforce? Evidence from a new type of data for German enterprises

Abstract: This empirical research note documents the relationship between composition of a firm's workforce (with a special focus on age and gender) and its performance with respect to innovative activities (outlays and employment in research and development (R&D)) for a large representative sample of enterprises from manufacturing industries in Germany using unique newly available data. We find that firms with a higher share of older workers have significantly lower proportions of R&D outlays in total revenues and of T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 20 publications
3
18
0
Order By: Relevance
“…The better performance of majority female-owned SMEs in manufacturing, accommodation and food services, and retail trade may be explained by the higher proportion of female employees in these industries. This explanation is confirmed by Pfeifer and Wagner (2014), who found that firms in German manufacturing industries with a higher share of female employees were more likely to be innovative.…”
Section: Employmentmentioning
confidence: 61%
“…The better performance of majority female-owned SMEs in manufacturing, accommodation and food services, and retail trade may be explained by the higher proportion of female employees in these industries. This explanation is confirmed by Pfeifer and Wagner (2014), who found that firms in German manufacturing industries with a higher share of female employees were more likely to be innovative.…”
Section: Employmentmentioning
confidence: 61%
“…Goebel and Zwick (2012) also find no significant age-productivity profiles once the endogeneity of the age structure of the workforce is taken into account by GMM estimates. Pfeifer and Wagner (2014a) obtain for manufacturing firms a positive concave age-productivity profile. Productivity increases until age 30 and does not significantly change afterwards.…”
Section: Increasing the Labor Force Participation Rate Of Older Workersmentioning
confidence: 90%
“…These employer provided pensions have been shown to reduce fluctuations in personnel (Rabe 2005;Schnabel and Wagner 2001) and to increase worker engagement (Bossler 2015). Finally, even though the age structure of the workforce may have little influence on productivity, a higher share of older workers appears to be associated with reduced profitability of German firms (Pfeifer and Wagner 2014a). Altogether, these facts suggest that deferred compensation plays an important role in the functioning of the labor market for older workers in Germany.…”
Section: German Evidencementioning
confidence: 99%
“…The balance of evidence on the relationship between age and innovation decisively points to a negative connection. Pfeifer and Wagner (2012) record a strong adverse impact of average age on several innovationlinked indicators. Schubert and Andersson (2015) find the age of an individual to be negatively related to their innovation performance, and Arntz and Gregory (2014) show that 17 of the gap in regional innovation performance in Germany is explained by demographic aging.…”
Section: Age and Innovationmentioning
confidence: 99%